Origins of a Low-Sulfur Superalloy Al2O3 Scale Adhesion Map - James Smialek (Crystals, 2021)
Low-sulfur single-crystal Ni-base superalloys have demonstrated excellent cyclic oxidation resistance due to improved Al2O3 scale adhesion. This derives from preventing deleterious interfacial sulfur segregation that occurs at common ppm levels of S impurity. Multiple hydrogen-annealing desulfurization treatments were employed to produce a continuum of levels demonstrating this oxidative transition, using 1 h cyclic oxidation at 1100 °C for 500 h to 1000 h. The sulfur content was determined by glow discharge mass spectrometry. The complete gravimetric database of 25 samples is revealed and correlated with sulfur content. Maximum adhesion (i.e., no weight loss) was achieved at ≤ 0.3 ppmw S, significant spallation (20–30 mg/cm2) above 2 ppmw, with transitional behavior between 0.3 and 2 ppmw S. A map suggested that adhesion was enabled when the total sulfur reservoir was less than one S atom per Ni interface atom. Equilibrium models further suggest that segregation may be minimized (~1% at 0.2 ppmw bulk), regardless of section thickness. 1st order adhesion effects have thus been demonstrated for PWA 1480 having no Y, Zr, or Hf reactive element dopants and no possibility of confounding reactive element effects. The results are compared with 2nd generation PWA 1484, Rene’N5, N6, and CMSX-4® SLS, all having Hf dopants.